Cemitério São José: história, memória e sensibilidades teresinenses - ROSA, Mariana Antão de Carvalho (2019)
The present work proposes to investigate the behaviors, social meanings and sensitivities with the dead in Teresina, from the inauguration of the São José Cemetery in 1859. It is understood that the construction of this sanitized public cemetery, initially separated from the urban perimeter of the capital is related to the publication of laws in Piaui's posture codes from 1854. These aimed, among other things, to normalize burial spaces throughout the province, thus changing the funeral practices of the population at that time. On the other hand, observing the way society cares for its dead, materialized in tombs, says a lot about that community, about its culture and religiosity, we seek to understand how the analysis of the object system that makes up the Cemetery St. Joseph helps to understand social treatment of the dead in Teresina in the second quarter of the nineteenth and early twentieth centuries. Finally, the research is being carried out in the city of Teresina, but it also sheds light on the sensibilities of Piaui men in general. As an example, at one time or another, the research extends to the interior of Piauí, specifically to the cities of Barras and Monsignor Gil.